Pro: Access to advanced therapies for severe asthma should be restricted to patients with satisfactory adherence to maintenance treatment. Issue 2 (June 2021) - Murphy, Anna C.; Boddy, Claire; Bradding, Peter
Inhaled corticosteroids (ICS) are the core component of asthma treatment and the only maintenance therapy known to prevent asthma death. There is currently no evidence that biologics prevent asthma death in people with asthma, and as such, biologics cannot be recommended as an alternative to ICS therapy. Taking the time to assess adherence and provide interventions and education to support patients in asthma self-management has been shown to improve patient outcomes. It is therefore our responsibility as healthcare professionals to ensure that patients are supported, educated and motivated to adhere to ICS therapy before progressing to biologic therapies. ICS save lives. It is therefore our responsibility as healthcare professionals to ensure that patients are supported, educated and motivated to improve poor ICS adherence before treatment is further escalated to biologic therapy .https://bit.ly/3o2q26i